2022
DOI: 10.3389/fsurg.2022.818347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Features and Outcomes of Appendectomy in Elderly vs. Non-Elderly: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe objective of this study is to compare clinical and surgical outcomes of appendectomy among elderly and non-elderly subjects.MethodsA systematic search was conducted on PubMed, Scopus, and Google academic databases. Studies, observational in design, that compared peri-and postoperative outcomes of appendectomy, in patients with acute appendicitis, between elderly and non-elderly/younger subjects were considered for inclusion. Statistical analysis was performed using STATA software.ResultsA total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was suggested that the risk of wound infections and intra-abdominal abscesses would rise after appendectomy in elderly patients. [ 13 ] In this study, however, it was observed that surgical complications were especially associated with the presence of at least two or more comorbidities preoperatively and lower Albs. Besides, post-operative hospitalization at the ICU was found to be more common in patients with surgical complications.…”
Section: Discussionmentioning
confidence: 57%
“…It was suggested that the risk of wound infections and intra-abdominal abscesses would rise after appendectomy in elderly patients. [ 13 ] In this study, however, it was observed that surgical complications were especially associated with the presence of at least two or more comorbidities preoperatively and lower Albs. Besides, post-operative hospitalization at the ICU was found to be more common in patients with surgical complications.…”
Section: Discussionmentioning
confidence: 57%
“…Though some studies have reported that extremes of age were associated with increased risk of adverse outcomes (Rahman et al 2020;Yuan et al 2022;Lasek et al 2018), age was not a significant factor in our study possibly because we did not have anyone less than 5 years, nor did we have anyone above the age of 65 years, the age groups associated with an increased risk of adverse outcomes (Rahman et al 2020;Yuan et al 2022;Lasek et al 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Though appendicitis has been associated with significant morbidity following surgery in other countries with better health structures (Talan and Saverio 2021;Rahman et al 2020), the outcomes in Uganda are not known but are expected to be different since the type of care offered has been shown to affect early outcomes (Yuan et al 2022). For example, laparoscopic surgery has been shown to reduce complications (Biondi et al 2016), yet laparoscopic appendectomy is not available in most facilities in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Though appendicitis has been associated with signi cant morbidity following surgery in other countries with better health structures (5,8), the outcomes in Uganda are not known. These outcomes are expected to be different since the type of care offered has been shown to affect early outcomes (9). For example, laparoscopic surgery has been shown to reduce complications (10), yet laparoscopic appendectomy is not available in most facilities in Uganda.…”
Section: Introductionmentioning
confidence: 99%